Current Status of the Steppe Eagle Population in the Republic of Kalmykia, Russia - Anton A. Abushin (Пернатые хищники и их охрана)
The article presents the results of the Steppe Eagle (Aquila nipalensis) population studies in 2022–2023. By 2023, 304 breeding territories were discovered, 39% of the estimated population size. The population size of the Northwestern Caspian region is probably higher than the average and close to its upper threshold of 1059 pairs, due to more than half of the breeding range not having been surveyed. The average occupancy rate was 74%, the success rate was 54%, and the density of breeding territories was 4.9 pairs/100 km². The proportion of young birds in breeding pairs is 28%. Three 391 nests were found, with an average of 1.71±0.70 nestlings per successful nest. Productivity and breeding success depend on the state of the food supply. Due to the high density of ground squirrels, the density of occupied and successful sites increased at the Kaskyrskaya and Khulkhutinskaya sites. At the Sarpinsky site, the density of occupied breeding territories was low, and breeding was unsuccessful. The loss of nestlings due to hunger at the late stages of supplementary feeding is at least 10%. After the post-fledgling dependence period, fledglings often become victims of road accidents and poachers. Mortality of adult eagles is mainly associated with electrocution on power lines (93%) and collision with automobiles on roads. About 76% of eagles reproduce with very low productivity and success, or do not reproduce due to the poor food supply. The prospects for preserving the species in the region, priority tasks and recommendations for further monitoring are discussed.